Identification of a Specific Role of Dihydrozeatin in the Regulation of the Cell Differentiation Activity in Arabidopsis Roots - Federico Vinciarelli; Mirko De Vivo; Alessio Terenzi; Francesca Cazzaniga; Samuele Amati; Pierpaolo Damato; Elena Salvi; Marta Del Bianco; Riccardo Di Mambro; Paolo Costantino; Sabrina Sabatini; Raffaele Dello Ioio (Plants)
The plant hormones cytokinins are a class of heterogeneous active compounds that control multiple aspects of development and physiology. Among cytokinins, trans-zeatin (tZ), the most abundant cytokinin, has been extensively studied in relation to its effects on development, and it plays a key role in promoting cell differentiation. In analogy with tZ, here we demonstrate that dihydrozeatin (DHZ) controls (root) development by promoting cell differentiation. By means of pharmacological and genetic analysis, we demonstrate that DHZ is specifically and uniquely perceived by the histidine kinase (HK) receptor AHK3, and that this interaction is sufficient to promote cell differentiation in the root meristem via activation of the transcription factors ARABIDOPSIS RESPONSE REGULATOR 1, 12, and 11. We also show that DHZ and tZ activity might be conserved among plants. Our results support the idea that different types of cytokinins act via specific receptors to exert their roles and suggest new approaches to study their activity in differentiation.